2019
DOI: 10.3390/ijerph16020289
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Insomnia Symptoms between Immigrants and Non-Immigrants in Switzerland attributed to Emotional Distress: Analysis of the Swiss Health Survey

Abstract: Migration can be a stressful experience and may lead to poor health and behavioral changes. The immigrant population in Switzerland is disproportionately burdened by several negative health outcomes, chief among these is mental health issues. The aim of the study was to investigate whether sleep disturbances are more prevalent among immigrants compared to non-immigrants and whether emotional distress might explain sleep differences. Based on the Swiss Health Survey 2012 dataset, we analyzed the data of 17,968 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Finally, we explore the possibility of a moderating role of a migration background on the studied association. Having a migration background was recently associated with negative sleep outcomes (Schneeberger et al, 2019). Students with a migration background might suffer more in terms of sleep quality due to their smartphone use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we explore the possibility of a moderating role of a migration background on the studied association. Having a migration background was recently associated with negative sleep outcomes (Schneeberger et al, 2019). Students with a migration background might suffer more in terms of sleep quality due to their smartphone use.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we explore the possibility of a moderating role of a migration background on the studied association. Having a migration background was recently associated with negative sleep outcomes (Schneeberger et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, simply analyzing cognitive or behavioral strengths neglects the role of emotional factors that can act as protective factors against mental health challenges. Schneeberger et al [18] reported data showing how the emotional distress suffered by immigrants had a negative effect on their insomnia in comparison to non-immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Based on data from the National Survey in Sweden 1996, Sundquist et al found that Bosnian refugee women on a group level had a much higher risk of undefined sleep difficulties than Swedish-born women, and Taloyan et al found that Kurdish men twice as often reported sleep difficulties, compared with the Swedish-born men [15,20,21]. A Swiss study found that the non-Western recent immigrants also, after many years of stay, reported more early awakening and trouble falling asleep, as compared with non-immigrants [22]. This finding was expected to be due to high levels of emotional distress.…”
Section: Introductionmentioning
confidence: 99%